Mesenchymal stem cells deliver exogenous miR‐21 via exosomes to inhibit nucleus pulposus cell apoptosis and reduce intervertebral disc degeneration. Issue 1 (14th August 2017) - Cheng, Xiaofei; Zhang, Guoying; Zhang, Liang; Hu, Ying; Zhang, Kai; Sun, Xiaojiang; Zhao, Changqing; Li, Hua; Li, Yan Michael; Zhao, Jie
Abstract: Although mesenchymal stem cells (MSCs) transplantation into the IVD (intervertebral disc) may be beneficial in inhibiting apoptosis of nucleus pulposus cells (NPCs) and alleviating IVD degeneration, the underlying mechanism of this therapeutic process has not been fully explained. The purpose of this study was to explore the protective effect of MSC‐derived exosomes (MSC‐exosomes) on NPC apoptosis and IVD degeneration and investigate the regulatory effect of miRNAs in MSC‐exosomes and associated mechanisms for NPC apoptosis. MSC‐exosomes were isolated from MSC medium, and its anti‐apoptotic effect was assessed in a cell and rat model. The down‐regulated miRNAs in apoptotic NPCs were identified, and their contents in MSC‐exosomes were detected. The target genes of eligible miRNAs and possible downstream pathway were investigated. Purified MSC‐exosomes were taken up by NPCs and suppressed NPC apoptosis. The levels of miR‐21 were down‐regulated in apoptotic NPCs while MSC‐exosomes were enriched in miR‐21. The exosomal miR‐21 could be transferred into NPCs and alleviated TNF‐α induced NPC apoptosis by targeting phosphatase and tensin homolog (PTEN) through phosphatidylinositol 3‐kinase (PI3K)‐Akt pathway. Intradiscal injection of MSC‐exosomes alleviated the NPC apoptosis and IVD degeneration in the rat model. In conclusion, MSC‐derived exosomes prevent NPCs from apoptotic process and alleviate IVD degeneration, at least partly, via miR‐21 contained in exosomes. Exosomal miR‐21 restrains PTEN and thus activates PI3K/Akt pathway in apoptotic NPCs. Our work confers a promising therapeutic strategy for IVD degeneration.